2023
DOI: 10.1038/s41598-023-38117-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of TOP2A in immunotherapy and vasculogenic mimicry in non-small cell lung cancer and its potential mechanism

Abstract: Type IIA topoisomerase (TOP2A) is significantly associated with malignant tumor development, invasion, treatment and its prognosis, and has been shown to be a therapeutic target against cancer. In contrast, the role of TOP2A in the immunotherapy of non-small cell lung cancer as well as in Vasculogenic mimicry (VM) formation and its potential mechanisms are unclear. The aim of this study was to investigate the role of TOP2A in proliferation, skeleton regulation, motility and VM production in non-small cell lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…showed that TOP2A positivity was associated with PD-L1 expression in NSCLC ( p < 0.001) [ 28 ]. TOP2A has been recently revealed to play an important role in immunotherapy and vasculogenic mimicry formation in NSCLC through the upregulation of PD‑L1 expression [ 29 ]. In the present study, we revealed that the knockdown of TOP2A again overturned the impact of sh-KCTD9 on the CD8 + cells and PD-L1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…showed that TOP2A positivity was associated with PD-L1 expression in NSCLC ( p < 0.001) [ 28 ]. TOP2A has been recently revealed to play an important role in immunotherapy and vasculogenic mimicry formation in NSCLC through the upregulation of PD‑L1 expression [ 29 ]. In the present study, we revealed that the knockdown of TOP2A again overturned the impact of sh-KCTD9 on the CD8 + cells and PD-L1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, high levels of TOP2A have been linked to more aggressive tumor behavior and later disease stages in several types of cancer such as HCC, 38 breast cancer, 36 and NSCLC 39 . Furthermore, upregulation of TOP2A is associated with a negative prognosis, increased tumor grades, and stages, suggesting its involvement in cancer aggressiveness 39,40 . Notably, chemotherapy that targets TOP2 enzymes, such as TOP2A, is often used to treat both solid tumors and blood cancers 40 .…”
Section: Discussionmentioning
confidence: 99%
“… 39 Furthermore, upregulation of TOP2A is associated with a negative prognosis, increased tumor grades, and stages, suggesting its involvement in cancer aggressiveness. 39 , 40 Notably, chemotherapy that targets TOP2 enzymes, such as TOP2A, is often used to treat both solid tumors and blood cancers. 40 However, the effectiveness of TOP2 inhibitors as primary chemotherapeutic agents is counteracted by the potential for secondary cancers and heart damage, underscoring the need for more accurate targeted approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ECs express both TopoIIa and IIb as they are proliferative in comparison to terminally differentiated non-proliferative cardiomyocytes, especially during stress-induced endothelial activation, wound healing, and angiogenesis [113]. Therefore, they are more vulnerable to Dox-inhibition of TopoII in addition to Dox-induced DNA intercalation and micronuclei generation.…”
Section: Dox-induced Endothelial Dysfunction Endotheliotoxicity and C...mentioning
confidence: 99%